Dense on Porous Solid LATP Electrolyte System: Preparation and Conductivity Measurement. Issue 1 (12th September 2016) - Duluard, Sandrine; Paillassa, Aude; Lenormand, Pascal; Taberna, Pierre‐Louis; Simon, Patrice; Rozier, Patrick; Ansart, Florence
Abstract : A dense membrane of lithium aluminum titanium phosphate Li1+ x Al x Ti2− x (PO4 )3, x = 0.3 (LATP) is deposited on a porous LATP substrate via wet chemistry. In the polymerized complex process, phosphate precursors with different active groups and steric hindrance are selected to tune precursor's reactivity. Rheological studies and microstructural observations lead to the selection of an LATP powder slurry charged with lithium, aluminum, titanium, and phosphate ion precursors. The optimized formulation is impregnated into a porous LATP substrate. After thermal treatment, dense LATP membranes on top of a porous LATP substrate are obtained with conductivities as high as 3 × 10 −4 S/cm for the dense part, the porous part acting as a mechanical support. An original Van der Pauw impedance setup is validated for the measurement of the ionic conductivity of such dense/porous systems.